Recent developments and the new direction in soft-computing foundations and applications : selected papers from the 7th World Conference on Soft Computing, May 29-31, 2018, Baku, Azerbaijan /: selected papers from the 7th World Conference on Soft Computing, May 29-31, 2018, Baku, Azerbaijan. (2020) - Unknown
No abstract available